中學生成長型思維與學習投入之關係： 以後設認知與羞愧感為中介變項 A Study on the Impact of Growth Mindset on Learning Engagement Among Junior and Senior High School Students: Exploring the Mediating Roles of Metacognition and Shame - 王佳琪 Chia-Chi Wang; 孫國瑋 Guo-Wei Sun (Journal of Research in Education Sciences, 2025)
在青少年時期維持學習投入對長期的學業成功相當重要。本研究探討中學生成長型思維與學習投入的關係，並檢驗後設認知與羞愧感的中介效果，以1,167位國、高中生為研究對象，完成「思維量表」、「後設認知量表」、「羞愧感量表」與「學習投入量表」等研究工具的填答，採結構方程模式（Structural Equation Modeling, SEM）進行分析。研究結果顯示，一、學生的成長型思維能正向預測後設認知、後設認知能直接正向預測學習投入、成長型思維會間接正向預測學生的學習投入；二、學生的成長型思維能直接負向預測羞愧感、羞愧感會直接負向預測學生的學習投入；三、學生的後設認知與羞愧感，在成長型思維與學習投入間具有中介效果。本研究驗證了成長型思維與中學生學習投入的關係機制，對於促進中學生的學習具有重要的意義。 Background and Purpose Maintaining learning engagement during adolescence is essential for long-term academic success. However, embracing challenges is a critical attitude that many domestic students lack. Taiwanese students face significant academic pressure, making it a key issue to help them interpret anxiety and stress during examinations with a positive mindset. This is particularly evident among junior and senior high school students, who are deeply influenced by an exam-oriented educational system. Academic achievement has become a primary criterion for evaluating their self-concept and self-worth (Liu & Lin, 2002). Although it is difficult to transform Taiwan’s educational landscape in the short term, guiding students to perceive examinations as opportunities for self-challenge and adopting a growth mindset to address the negative emotions associated with academic pressure can alleviate feelings of anxiety and stress. Such an approach can also enhance adolescents’ psychological resilience, enabling them to better cope with future challenges and setbacks (Tang et al., 2015). Therefore, focusing on strategies to strengthen students’ psychological capacity is critical for their long-term development. Nevertheless, previous studies have not adequately explored the potential mediating mechanisms through which a growth mindset influences learning engagement, leaving an important research gap. In response to this, the present study aims to investigate the impact of a growth mindset on learning engagement among junior and senior high school students, with a particular focus on the mediating roles of metacognition and shame.